Bone morphogenetic protein‐7 (BMP‐7) augments insulin sensitivity in mice with type II diabetes mellitus by potentiating PI3K/AKT pathway. (10th February 2017) - Chattopadhyay, Tandrika; Singh, Rajiv Ranjan; Gupta, Sarika; Surolia, Avadhesha
Abstract: A direct link between development of insulin resistance and the presence of chronic inflammation, in case of obesity exists, with cytokines playing an important role in glucose metabolism. Members of TGF‐β superfamily, including bone morphogenetic proteins (BMPs), have been shown to be involved in islet morphogenesis, establishment of β‐cell mass and adipose cell fate determination. Here, we demonstrate a novel and direct role of BMP‐4 and ‐7 in the regulation of glucose homeostasis and insulin resistance. An age‐dependent increase in serum BMP‐4 and decrease in serum BMP‐7 levels was observed in animal models of type II diabetes. In this study, BMP‐7 and ‐4 have been demonstrated to have antagonistic effects on insulin signaling and thereby on glucose homeostasis. BMP‐7 augmented glucose uptake in the insulin sensitive tissues such as the adipose and muscle by increasing Glut4 translocation to the plasma membrane through phosphorylation and activation of PDK1 and Akt, and phosphorylation and translocation of FoxO1 to the cytoplasm in liver/HepG2 cells. Restoration of BMP‐7 levels in serum of diabetic animals resulted in decreased blood glucose levels in contrast to age matched untreated control groups, opening up a new therapeutic avenue for diabetes. On the contrary, BMP‐4 inhibited insulin signaling through activation of PKC‐θ isoform, and resulted in insulin resistance through the attenuation of insulin signaling. BMP‐7 therefore is an attractive candidate for tackling a multifaceted disease such as diabetes, since it not only reduces body fat, but also strengthens insulin signaling, causing improved glucose uptake and ameliorating peripheral insulin resistance. © 2017 BioFactors, 43(2):195–209, 2017